2006
DOI: 10.1177/154405910608500910
|View full text |Cite
|
Sign up to set email alerts
|

S100A8 Triggers Oxidation-sensitive Repulsion of Neutrophils

Abstract: The inflammatory response to tissue injury is a multi-faceted process. During this process, neutrophils migrate in the extravascular spaces, directed to the site of injury by chemical gradients generated by chemotactic molecules. S100A8, a protein associated with a wide variety of inflammatory conditions, is heavily over-expressed in association with inflammation. We hypothesized that human S100A8 possesses neutrophil-repelling properties that result in an antiinflammatory effect in vivo. The chemotactic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 27 publications
(24 reference statements)
4
44
0
Order By: Relevance
“…In our previous work, we showed that calprotectin inhibits the recruitment of neutrophils and their oxidative metabolism (Sroussi et al, 2006(Sroussi et al, , 2010. It is tempting to speculate that vitamin D deficiency may therefore produce an exaggerated calprotectinemia which would then depress neutrophil responsiveness, contributing to a higher risk of OC.…”
Section: Discussionmentioning
confidence: 97%
“…In our previous work, we showed that calprotectin inhibits the recruitment of neutrophils and their oxidative metabolism (Sroussi et al, 2006(Sroussi et al, , 2010. It is tempting to speculate that vitamin D deficiency may therefore produce an exaggerated calprotectinemia which would then depress neutrophil responsiveness, contributing to a higher risk of OC.…”
Section: Discussionmentioning
confidence: 97%
“…93 recruitment into the murine air-pouch in response to LPS, indicating antiinflammatory effects. 74 More recently, these investigators found that intravenous injection of S100A8/A9 into endotoxemic mice reduced neutrophil infiltration into organs; markers of oxidative damage decreased and survival rates doubled. The suggested mechanism was via S100A8 binding TLR4, an interaction that may interfere with protease-activated receptor-2 (PAR-2) cooperation with TLR4, to reduce the magnitude of inflammation.…”
Section: Extracellular Functions and Receptors Of Calgranulinsmentioning
confidence: 99%
“…67 The calgranulins have been reported to induce proinflammatory cytokines in monocytes/macrophages 68, 69 and are implicated in promoting EC adhesion and dysfunction, 70-72 and affecting SMC proliferation. 49, 73 However, S100A8 and S100A9 at physiological levels have neutrophil-repulsion activity, 74 and reduce the spontaneous and stimulated neutrophil oxidative burst, possibly mediated by adenosine metabolites. 75 The calgranulin receptors remain an enigma.…”
Section: Extracellular Functions and Receptors Of Calgranulinsmentioning
confidence: 99%
“…S100A8 is a potent scavenger of peroxide and hypochlorite generated by activated neutrophils and macrophages (28,29). The chemotactic activity of murine (m)S100A8 is altered upon oxidation (28), and human (h)S100A8 has an anti-inflammatory, neutrophil-repelling property that is also oxidation sensitive (30).…”
mentioning
confidence: 99%